Determination of some thermodynamic parameters of poly(styrene-graft-ethyl methacrylate) using inverse gas chromatography - Temüz, MM; Coskun, M; Açikses, A (Taylor & Francis Inc, 2006)
In this study, the specific retention volumes, V-g(o) , were determined for poly(styrene-g-ethly methacrylate) obtained from grafting of poly(styrene-co-p-chloromethyl styrene) having a 54% (by mole) chlorine content with ethyl methacrylate and a series of nonsolvent as probe, five n-alkans, five alcohols and carbon tetrachloride, with the aid of inverse gas chromatography, in a temperature range of 333 to 463 K. Some thermodynamic properties, such as the sorption enthalpy, Delta H-s , sorption free energy, Delta G(s) , sorption entropy, Delta S-s , in the 373-403 K temperature range, the partial molar free energy, Delta G(infinity), and the partial molar heat of mixing, Delta H-infinity , in the temperature 413-463 K range, were calculated from the relationships between the specific retention volumes and related properties. The weight fraction activity coefficients of probes as logarithmic value, ln Omega(infinity)(1), and Flory-Huggins interaction parameters, chi(infinity)(12) , between the polymer and probes, were estimated. Also, the glass transition temperature, T-g, and the solubility parameter, delta(2), of the graft copolymer, were found to be about 85 degrees C, and between 5.0-6.8 (cal/cm(3))(1/2) in the 413-463 temperature range K, respectively, and some extrapolations to room temperature were done and the results were discussed.
Keywords: graft copolymer; poly(ethyl methacrylate); thermodynamic properties; inverse gas chromatography